Higher farmer willingness to pay for quality cassava (Manihot esculenta Crantz) planting materials: evidence from experimental auctions in Cambodia and Lao PDR. Replication data including socioeconomic survey and experimental auction results - Delaquis, Erik; Mienmany, Bandit; Slavchevska, Vanya Mihova; Almekinders, Conny J. M.; Newby, Jonathan Craig; Sareth, Chea; Tanthapone, Chanpasouk; Struik, Paul C. (2024)
Data includes paired socioeconomic survey responses and results from experimental auctions for cassava planting material in Cambodia (4 provinces, N=321) and Lao PDR (5 provinces, N=391). This information was gathered to measure farmer demand / willingness to pay for different classes of cassava planting material with different traits. The goal of the activity was to understand farmer behavior and preferences surrounding seed purchase and exchange. Metodology:Surveys and auction responses were gathered between 10 November, 2020 and 5 April, 2021, from cassava growing households across the major cassava production areas of both countries. Post-survey auctions were conducted on groups of 20 participants with three experimental products: farmer seed, an elite cassava variety less susceptible to cassava mosaic disease, and the same elite variety tested and virus-free. Participants placed bids for the maximum they would pay for a single 20 stem bundle of planting material of each product in a single full round, silent bidding approach. The study was designed to elicit farmer willingness to pay for improved planting materials.